The Roma in Post-Communist Bulgaria: Growing Social Marginalization and State Policies - Yorgos Christidis (Journal of Asian Social Science Research, 2020)
This article analyzes the growing impoverishment and marginalization of the Roma in Bulgarian society and the evolution of Bulgaria’s post-1989 policies towards the Roma. It examines the results of the policies so far and the reasons behind the “poor performance” of the policies implemented. It is believed that Post-communist Bulgaria has successfully re-integrated the ethnic Turkish minority given both the assimilation campaign carried out against it in the 1980s and the tragic events that took place in ex-Yugoslavia in the 1990s. This Bulgaria’s successful “ethnic model”, however, has failed to include the Roma. The “Roma issue” has emerged as one of the most serious and intractable ones facing Bulgaria since 1990. A growing part of its population has been living in circumstances of poverty and marginalization that seem only to deteriorate as years go by. State policies that have been introduced since 1999 have failed at large to produce tangible results and to reverse the socio-economic marginalization of the Roma: discrimination, poverty, and social exclusion continue to be the norm. NGOs point out to the fact that many of the measures that have been announced have not been properly implemented, and that legislation existing to tackle discrimination, hate crime, and hate speech is not implemented. Bulgaria’s political parties are averse in dealing with the Roma issue. Policies addressing the socio-economic problems of the Roma, including hate speech and crime, do not enjoy popular support and are seen as politically damaging.